Environmental tax law and greenwashing: the moderating role of digitization - Yating Ding; Xudong Wang; Lin Wu (Humanities & Social Sciences Communications)
Abstract Greenwashing, as a deceptive market behavior, not only undermines market order and credibility but also damage the environment. How to curb greenwashing is a critical issue for China as it enters an economic transition period and strives for sustainable development. In 2018, China implemented the Environmental Tax Law, imposing pollution fees on polluting enterprises for the first time in the form of mandatory taxation. Whether this measure can enhance real environmental benefits and curb greenwashing behaviors of companies is worth exploring. This paper utilizes panel data from listed companies from 2015 to 2021 and employs a Difference-in-Differences model to investigate the impact of the environmental tax law on greenwashing. Empirical results demonstrate that environmental tax law can effectively suppress greenwashing among heavily polluting enterprises. The Double Machine Learning model similarly validates this outcome. To explore the influence of mechanisms, we analyze the moderating effects of multidimensional (company, society, and government) digitization and confirm the dominant moderating role of government digitization. Furthermore, heavily polluting enterprises, particularly those in regions with higher tax rates, those required to disclose information, and high-tech firms, are more susceptible to the influence of environmental tax law in adopting real green production practices. This study confirms the positive role of environmental tax law and introduces the comprehensive digitalization moderation mechanism for the first time, providing important insights for China’s green transition and regional environmental governance.